Identifikasi Morfologi dan Perilaku Makan Kambing Marica yang Dipelihara di Luar Habitat - Ngitung, Rosdiana; Taiyeb, Mushawwir; Idris, Irma Suryani (bionature, 2020)
Abstract. This research is a descriptive study that aims to determine the morphological characteristics of Marica goats. That are kept outside the habitat. Observation of morphological characteristics and eating activities using 2 goats (1 male and 1 female). This research was conducted at the Biology Experiment Garden in Makassar State University. The results obtained by Marica Goat have a relatively small body dimensions, upright ears and relatively small short, short and small horns and look agile and aggressive and Marica goats during the day (09.00-16.00) do more eating activities. Keywords: Marica Goat, morphological characteristicsm and eating activities.